“You’re telling us to go first?!” COVID-19 pandemic and vaccination experiences among Aboriginal adults in Western Australia - Samantha J. Carlson; Carla Puca; Paige Wood-Kenney; Justin Kickett; Valerie Swift; Katie Attwell; Christopher C. Blyth (Humanities & Social Sciences Communications)
Abstract Globally, Indigenous populations have been disproportionately impacted by pandemics. In Australia, though national infection rates with COVID-19 infections in Aboriginal and/or Torres Strait Islander people were lower in the first 12 months of the COVID-19 pandemic, there was soon a greater burden in Aboriginal and/or Torres Strait Island people once Omicron was circulating. Uptake of the COVID-19 vaccine was also lower among Aboriginal and/or Torres Strait Islander people. It was imperative to understand the stories of Aboriginal and/or Torres Strait Islander people in WA about their experience of the COVID-19 pandemic and vaccine rollout. Between September 2022 and October 2023, we conducted five face-to-face yarning workshops with Aboriginal and/or Torres Strait Islander people in Noongar Whadjuk Boodja (Perth metropolitan region, Western Australia). Yarns discussed COVID-19 experiences, knowledge and attitudes about COVID-19 and vaccination, reasons for or against COVID-19 vaccination, trusted sources of information, and knowledge of COVID-19 vaccination programmes for Aboriginal and/or Torres Strait Islander people. Data was thematically analysed in an inductive manner on NVivo, followed by a data interpretation forum with study investigators and community members. Across the five yarning workshops, we heard the stories and experiences of 38 Aborginal and/or Torres Strait Islander people. Many described the negative impact that the policies implemented to control COVID-19 had on their ability to connect with their community and practice traditional culture. Very few participants trusted government and any government information due to both historical and contemporary factors. This led participants to be wary of the fact they were among the first to be prioritised for COVID-19 vaccination in Australia. Though most participants (92%) had received at least one COVID-19 vaccine, there were high levels of COVID-19 vaccine hesitancy. The main reason for this was due to COVID-19 vaccine mandates; participants were, in essence, coerced acceptors of what they felt to be an unsafe vaccine that provided little protection against a mild disease. Our yarns identified high levels of COVID-19 vaccine hesitancy and circulation of misinformation amongst Perth-based Aboriginal and/or Torres Strait Islander people. Our findings also demonstrate that there were many unintended consequences of COVID-19 policies on Aboriginal and/or Torres Strait Islander people and culture. Future pandemic policies and vaccine programmes must consider the impact on not only the health of Aboriginal and/or Torres Strait Islander people but also the impact on community and culture.